2022
DOI: 10.1186/s12886-022-02327-9
|View full text |Cite
|
Sign up to set email alerts
|

Do limbal relaxing incisions during cataract surgery still have a role?

Abstract: Background Though Limbal Relaxing Incisions (LRI) were used widely to correct pre-existing corneal astigmatism during cataract surgery, they have been replaced recently with the more expensive methods like the use of toric Intra Ocular Lenses (IOL) and femtosecond during cataract surgery. We conducted our study to re-evaluate the role of (LRI) in correcting pre-existing moderate corneal astigmatism during cataract surgery in settings where other options are neither available nor affordable. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Several studies have shown that FLLRIs provides a higher correction index and a smaller variance vector than manual LRI [ 44 , 49 ]. Therefore, we believe that FLLRIs is an excellent way to reduce astigmatism in patients, which is similar to the conclusions of the existing literature [ 50 ].…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have shown that FLLRIs provides a higher correction index and a smaller variance vector than manual LRI [ 44 , 49 ]. Therefore, we believe that FLLRIs is an excellent way to reduce astigmatism in patients, which is similar to the conclusions of the existing literature [ 50 ].…”
Section: Discussionsupporting
confidence: 90%
“…The mean corneal astigmatism was 1.2 D in the present study and part of the observed residual SE is related to this astigmatism. The refractive error will not be completely corrected when there is significant corneal astigmatism not corrected by a toric IOL [36] or relaxed incision [37] or if an implanted toric IOL rotates over time [38] . Achieving the postoperative SE near Plano is the basis for calculating spherical IOL power by most IOL power calculation formulas if astigmatism correction is not planned.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the limitations of astigmatism-correcting steep-axis incisions, other options for correction of corneal astigmatism should be taken into account. There are multiple procedures to correct astigmatism in patients with cataract, including toric intraocular lenses (IOLs) [ 30 ], keratotomy [ 31 , 32 ], limbal relaxing incisions (LRI) [ 33 ], excimer laser in situ keratomileusis [ 34 ], etc. Like relaxing incisions from the steep axis, toric IOLs have been widely applied in the correction of astigmatism, especially moderate to severe astigmatism, in cataract surgeries [ 35 ].…”
Section: Discussionmentioning
confidence: 99%